Pelanggaran Kode Etik Advokat dalam Pembuatan Surat Kuasa - Sari Aprilianti; Suwari Akhmaddhian (Universitas Kuningan, 2019)
The purpose of this study is to find out how the form of accountability of an advocate for violations of the code of ethics in the power of attorney. The research method used is normative juridical, which is an approach method by studying the law which is conceptualized as a norm or rule that applies in society, and serves as a reference for everyone's behavior. data collection tool through library research. ata used secondary, that is data obtained through the study of documentation by reading scientific books, magazines, internet, newspapers and other readings related to research. The results of the study are violations given to Advocates not only refer to Law No. 18 of 2003 but are regulated in the Advocate Code of Ethics where in article 16 (1) the Advocate Code of Ethics given by the Organization to Advocates is almost the same as article 7 paragraph (1) Law No. 18 of 2003 which in article 16 paragraph (1) of the Advocate Code of Ethics states that